Effect of Food with Low Enrichment of N-3 Fatty Acids in a Two-Month Diet on the Fatty Acid Content in the Plasma and Erythrocytes and on Cardiovascular Risk Markers in Healthy Young Men - Jaček, Martin; Hrnčířová, Dana; Rambousková, Jolana; Dlouhý, Pavel; Tůma, Petr (Nutrients, 2020)
Polyunsaturated fatty acids of the n-3 series (n-3 PUFA) exhibit a number of favorable effects on the human organism and it is desirable to increase their intake in the diet. For this purpose, flaxseed oil was added to a chicken-feed mixture for the production of meat and eggs. The content of n-3 PUFA in the obtained meat was increased from 250 mg (reference value) to 900 mg in 100 g of meat and from 110 mg (reference value) to 190 mg in 100 g of whole egg; the enriched products are designated as omega-3 meat and omega-3 eggs. Omega-3 meat and eggs were subsequently fed for a period of eight weeks in an amount of 480 g of meat and four eggs (228 g netto) a week to a group of 14 healthy volunteers, whose body composition parameters were measured and blood was analyzed biochemically to determine blood lipids, coagulation parameters, plasma, and erythrocyte fatty acid spectrum composition. A control group of 14 volunteers was fed normal chicken and eggs in the same regime. The performed dietary intervention increases the intake of long-chain PUFA (LC-PUFA) by 37 mg per day, which represents 7-15% of the recommended daily dose. The performed tests demonstrated that the consumption of omega-3 enriched meat and eggs significantly increases the content of n-3 PUFA in the erythrocytes, which are a long-term indicator of fatty acid intake. This intervention has no demonstrable effect on the basic body parameters, such as body weight, fat content, Body Mass Index (BMI), and also on the plasma cholesterol level, high-density lipoprotein (HDL), low-density lipoprotein (LDL), blood clotting and inflammation markers, and omega-3 index.
Keywords: erytrocyty; lidé; mladiství; Adult; Fatty Acids, Omega-3; Lipoproteins, LDL; maso; omega-3 mastné kyseliny; kardiovaskulární nemoci; Single-Blind Method; Heart Disease Risk Factors; Lipoproteins, HDL; vejce; Healthy Volunteers; Body Mass Index; Meat; lipoproteiny HDL; Adolescent; Humans; index tělesné hmotnosti; rizikové faktory kardiovaskulárních chorob; Erythrocytes; dieta; mastné kyseliny; Food, Fortified; fortifikované potraviny; mužské pohlaví; mladý dospělý; Cardiovascular Diseases; Diet; lipoproteiny LDL; Young Adult; Eggs; jednoduchá slepá metoda; Fatty Acids; Male; dospělí; zdraví dobrovolníci pro lékařské studie